Feasibility and oncologic safety of low ligation of inferior mesenteric artery with D3 dissection in cT3N0M0 sigmoid colon cancer - Lee, Kyung Ha (Ann Surg Treat Res, 2018)
PURPOSE: There is no standard consensus for the ligation level of the inferior mesenteric artery during radical resection of sigmoid colon cancer. Especially, there is little research about low ligation combined with D3 dissection. The study was performed to compare feasibility and oncologic safety between low ligation with D3 dissection to high ligation in intermediately advanced sigmoid colon cancer. METHODS: From January 2008 to December 2013, 134 patients who underwent radical surgery for cT3N0M0 sigmoid colon cancer were evaluated retrospectively. Clinicopathologic factors and oncologic outcomes of high ligation (HL, n = 51) and low ligation (LL, n = 83) groups were compared. RESULTS: The mean operative time was significantly shorter in LL, and there was no difference in complications, distal margin or number of retrieved lymph node. The tumor size was significantly larger in HL, but there was no difference in number of metastatic lymph node, pT or pN stage. There was no difference in overall survival, disease-free survival, or local and systemic recurrence. CONCLUSION: In cT3N0M0 sigmoid colon cancers, we suggest that low ligation with D3 dissection can be performed with feasibility and oncological safety.